Percepciones de los estudiantes de Comunicación sobre las fake news como recurso en el periodismo satírico - Segovia Pérez, Samara Rubi; Frías López, Aurora Kristell (Cinzontle, 2021)
The objective of this research is to analyze the perception of Comunication students about the function and impact of fake news and the perception of dissemination students in the construction of social reality from the theoretical perspective of social representations. The study was carried out with students from a public university in Tabasco that offers a degree in Communication. Two data collection techniques were used, the survey and semi-structured interviews applied to a representative sample of students, and four local journalists were interviewed. Among the findings, it is concluded that students are aware of the fake news on the site, but they share it for expression and fun, although both students and professionals are aware of the damage it causes in some.